Knowledge Management Capabilities As Predictor Of Project Performance In Malaysian Construction Companies - Tufail, Muhammad Asim (2013)
To understand the success and failure of knowledge management (KM), KM capabilities must be identified and assessed. Literature has offered theoretical grounding with regard to organizational capabilities as predictor of KM performance. In order to make KM more effective this study attempts to integrate the fragmented KM perspectives into the holistic framework including, knowledge infrastructure capability (technology, structure, and culture) and knowledge process capability (acquisition, conversion, application, and protection), based on Gold's (2001) study and project performance from the standpoint of time, cost, quality and safety in addition to project benefits. To bridge the gap between theory and practice, this study aligns unit of analysis more closely with the practitioners’ level of implementation by selecting project based organization (PBO), namely construction organization as population. The sample of 85 useable respondents was collected through Cohen’s (1988) statistical power and sample size conventions, from G7 Companies listed with CIDB. The regression analysis was conducted through partial least squares structural equation modelling using SmartPlS© software. The results of this study indicated that there is a positive relationship between effective KM and performance. The results of this study are valuable in establishing a valid and reliable survey instrument for construction companies, as well as in providing strong evidence that KM capabilities are essential to improving performance. It also recommends direction for future related studies.